Quantitative inspiratory–expiratory chest CT to evaluate pulmonary involvement in pediatric hematopoietic stem‐cell transplantation patients. Issue 5 (23rd December 2020) - Pennati, Francesca; Walkup, Laura L.; Chhabra, Anuj; Towe, Christopher; Myers, Kasiani; Aliverti, Andrea; Woods, Jason C.
Abstract: Pulmonary complications following allogeneic hematopoietic stem‐cell transplantation (HSCT) are a significant source of morbidity and complications may arise from a myriad of infectious and noninfectious sources. These complications may occur soon or many months post‐transplantation and can have a broad range of outcomes. Surveillance for pulmonary involvement in the pediatric HSCT population can be challenging due to poor compliance with clinical pulmonary function testing, primarily spirometry, and there may be a role for clinical imaging to provide an additional means of monitoring, particularly in the era of clinical low‐dose computed tomography (CT) protocols. In this single‐site, retrospective study, a review of our institution's radiological and HSCT databases was conducted to assess the utility of a quantitative CT algorithm to describe ventilation abnormalities on high‐resolution chest CT scans of pediatric HSCT patients. Thirteen non‐contrast enhanced chest CT examinations acquired both in inspiration and expiration, from 12 deceased HSCT patients (median age at HSCT 10.4 years, median days of CT 162) were selected for the analysis. Also, seven age‐matched healthy controls (median age 15.5) with non‐contrast‐enhanced inspiration–expiration chest CT were selected for comparison. We report that, compared to healthy age‐matched controls, HSCT patients had larger percentages of poorly ventilated (median, 13.5% vs. 2.3%, p  < .001) and air trapped (median 12.3% vs. 0%, p  < .001) regions of lung tissue, suggesting its utility as a potential screening tool. Furthermore, there was wide variation within individual HSCT patients, supporting the use of multivolume CT and quantitative analysis to describe and phenotype post‐transplantation lung involvement.